Stroke unit admission is associated with better outcome and lower mortality in patients with intracerebral hemorrhage. (6th March 2020) - Ungerer, M. N.; Ringleb, P.; Reuter, B.; Stock, C.; Ippen, F.; Hyrenbach, S.; Bruder, I.; Martus, P; Gumbinger, C.; ,
Abstract : Background and purpose: There is no clear consensus among current guidelines on the preferred admission ward [i.e. intensive care unit (ICU) or stroke unit (SU)] for patients with intracerebral hemorrhage. Based on expert opinion, the American Heart Association and European Stroke Organization recommend treatment in neurological/neuroscience ICUs (NICUs) or SUs. The European Stroke Organization guideline states that there are no studies available directly comparing outcomes between ICUs and SUs. Methods: We performed an observational study comparing outcomes of 10 811 consecutive non‐comatose patients with intracerebral hemorrhage according to admission ward [ICUs, SUs and normal wards (NWs)]. Primary outcomes were the modified Rankin Scale score at discharge and intrahospital mortality. An additional analysis compared NICUs with SUs. Results: Treatment outside an SU was associated with higher odds for an unfavorable outcome [ICU vs. SU: odds ratio (OR), 1.27; 95% confidence interval (CI), 1.09–1.46; NW vs. SU: OR, 1.28; 95% CI, 1.08–1.52] and higher odds for intrahospital mortality (ICU vs. SU: OR, 2.11; 95% CI, 1.75–2.55; NW vs. SU: OR, 1.52; 95% CI, 1.23–1.89). A subgroup analysis of severely affected patients treated in dedicated NICUs (vs. SUs) showed that they had a lower risk of a poor outcome (OR, 0.45; 95% CI, 0.26–0.79). Conclusions: Treatment in SUs was associated with better functional outcome and reduced mortality compared with ICUs and NWs. Our findings support the current guideline recommendations to treat patients with intracerebral hemorrhage in SUs or NICUs and suggest that some patients may further benefit from NICU treatment.